2020
DOI: 10.1016/j.brs.2020.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic translocation of protons out of penumbral neurons is protective in a rodent model of focal cerebral ischemia

Abstract: a b s t r a c tBackground: Intracellular acidosis in the ischemic penumbra can contribute to further cell death, effectively enlarging the infarct core. Restoring the acid-base balance may enhance tissue survivability after cerebral ischemia.Objective: This study investigated whether translocating protons out of penumbral neurons could mitigate tissue acidification and induce neuroprotection in a rodent model of acute cerebral ischemia. Methods: We modulated the penumbral neurons via a light-driven pump to tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 85 publications
0
11
0
Order By: Relevance
“…Registration of pH changes in brain tissues during acidosis of tissues has already been carried out earlier using various approaches. For example, synthetic fluorescent pH probes have previously been used, some of them were suitable for spatio-temporal signal resolution in superficial brain tissues of anesthetized animals [ 67 , 68 ]. Many of the limitations associated with the disadvantages of pH-imaging using synthetic dyes have been overcome with the advent of positron emission tomography (PET) and magnetic resonance imaging (MRI) [ [69] , [70] , [71] , [72] , [73] ].…”
Section: Discussionmentioning
confidence: 99%
“…Registration of pH changes in brain tissues during acidosis of tissues has already been carried out earlier using various approaches. For example, synthetic fluorescent pH probes have previously been used, some of them were suitable for spatio-temporal signal resolution in superficial brain tissues of anesthetized animals [ 67 , 68 ]. Many of the limitations associated with the disadvantages of pH-imaging using synthetic dyes have been overcome with the advent of positron emission tomography (PET) and magnetic resonance imaging (MRI) [ [69] , [70] , [71] , [72] , [73] ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that mild to moderate acidosis may be neuroprotective, while severe acidosis often leads to cerebral edema and worse functional outcomes. , However, the shortage supplement of oxygen and massive release of glutamate in the brain tissue may result in severe acidosis, and the mutual interaction of glutamate excitotoxicity and acidosis aggravates the brain damage during the ischemic stroke. Consistent with the observations that inhibition of the acidosis is neuroprotective, ,, the neuroprotectant of TRIOL reverses the intracellular acidification and neuronal injury in vitro (Figures –) and protects the brain from the ischemic damage (Figure ). Furthermore, in addition to the multiple effects of TRIOL on inflammation, excitotoxicity, and oxidative stress, the capability of suppression acidosis induced by glutamate as shown here and by hypoxia may explain the superiority of TRIOL over ion channel blocker MK801 and free radical scavenger edaravone in attenuating the ischemic brain damages (Figures –).…”
Section: Resultsmentioning
confidence: 85%
“…Accumulated evidence from animal and human studies demonstrates that apoptosis, autophagy, acidosis, etc., contribute to the overall pathologenesis following brain injury [77][78][79], interventions targeting these factors also show marked prospects for brain injury treatment. In 2020, Bo et al [80] transferred protons out of penumbra neurons and explored whether the proton-transfer could mitigate tissue acidification and induce neuroprotection after focal cerebral ischemia in rats. In this study, the penumbral neurons were regulated by an optical-driven pump (archaerhodopsin/ArchT group) or channel (rhodopsin-2/ChR2 group).…”
Section: Optogenetics In Protecting Neural Cellsmentioning
confidence: 99%